The structure evolution of hollow SiOC ceramic microspheres prepared with solvothermal method. Issue 3 (1st February 2023) - Xia, Kedong; Li, Chuangchuang; Zhang, Hui; Zhao, Siyu; Li, Weichen; Han, Fang; Li, Yuwei; Liu, Xiao
Abstract: Hollow silicon oxycarbide (SiOC) ceramic microspheres were synthesized through solvothermal process of vinyltriethoxysilane in NaOH solution with subsequent pyrolysis at high temperature. Increasing the synthesis temperature not only reduces the Si–C bond and C content in SiOC ceramics, but also transforms the amorphous SiOC ceramics into cristobalite SiO2 after carbonization. The rearrangement reaction of oxygen-enriched structural units results in the increase of SiO2 C2 unit. No phase separation occurs at 1400 °C, and SiC nanocrystals are mainly come from the carbothermal reduction reaction of SiO2 with free C. The size change of SiO2 nanograins were further investigated by HF etching. The porous carbon is obtained after removal of SiO2, while HF etching has no effect on the structure of free C. The C content affects the structure evolution of SiOC ceramics significantly. Although the size of SiO2 grows as increase of pyrolysis temperature, the high C content inhibits the crystallization and growth of SiO2 during the pyrolysis process.